Future Perspectives of the Implementation of EU Urban Agenda - Olejnik, Aleksandra (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
This article is an overview of opinions and recommendations adopted in the European Union vis-à-vis urban policy. The author analyses the Pact of Amsterdam and future perspectives of the implementation of EU Urban Agenda.